Macrolevel Analysis of Labour Productivity Losses Associated With Breast Cancer Among Women in 47 African Countries - Mustapha Immurana; Ibrahim Abdullahi; Kingsford Norshie; Elvis Reindolf Kale; Abdul-Aziz Iddrisu; Irene Honam Tsey; Evelyn Acquah; Maxwell Ayindenaba Dalaba (Global Health, Epidemiology and Genomics)
Conclusion: There is a need to enhance measures towards breast cancer prevention and control in Africa such as timely diagnosis, all-inclusive management of breast cancer, health promotion geared towards early detection and the creation of dependable referral systems to significantly reduce its associated LP losses.